DIFFUSE LARGE B-CELL LYMPHOMA-ASSOCIATED-RETINOPATHY CHARACTERIZED BY MINIMAL MORPHOLOGIC CHANGES AND SEVERE FUNCTIONAL IMPAIRMENT. (2017) - Moyal, Laura; Zambrowski, Olivia; Thirkill, Charles; Bottin, Caroline; Blanco, Rocio; Haioun, Corinne; Souied, Eric H.
Abstract : Purpose: To report the case of a patient whose retinal disease was found to be associated with a diffuse large B-cell lymphoma found 30 years after the apparent successful treatment of a classical Hodgkin lymphoma. Methods: Observational case report. Results: The authors describe the case of a 69-year-old man referred to their Department because of progressive, bilateral vision loss over the last few months. Deterioration in color vision and intense photophobia were also present. His best-corrected visual acuity was 20/400 in the right eye (RE) and 20/800 in the left eye (LE). Slit lamp and fundus examination failed to show any abnormalities. Spectral domain optical coherence tomography (SD-OCT) detected diffuse attenuation of the ellipsoid layers in addition to a focal subfoveal defect in both eyes. Both fluorescein and indocyanine angiographies (FA and ICGA) were normal. Full flash electroretinogram (ERG) revealed bilateral cone rod dysfunction with decreased amplitudes of both a and b waves. Conclusion: Because of the late onset of the disease, poor visual acuity compared with a small macular anatomical lesion and a history of Hodgkin lymphoma 30 years ago, a neoplastic etiology was investigated. Poor performance status and chest pain led to a thoracic CT scan, which identified a massive mediastinal tumor. Serum analysis found an abnormal amount of antibody activity within the 40 kD region of Western blot of retina. The diagnosis of diffuse large B-cell lymphoma was established. Systemic examinations found a Stage IV non-Hodgkin lymphoma. Abstract : The authors report the case of a patient presenting with severe vision loss, suspected to be a paraneoplastic syndrome secondary to a diffuse large B-cell lymphoma. Imaging could not explain the visual symptoms but full flash electroretinography revealed a cone rod dysfunction. Immunologic examination implicated a form of lymphoma-associated retinopathy (LAR).